Epidemiological determinants of road traffic accidents: a cross sectional study in Amravati, Maharashtra, India - Kizhatil, Anuradha; Jawarkar, A. K.; Lokare, Pushpa; Deotale, Manjusha (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic accidents (RTAs) represents a major epidemic of non-communicable disease in the present century affecting families, community and nation as a whole. Objectives was to study the epidemiological determinants of RTAs. Methods: A hospital based study of RTA victims was conducted for a period of one year at the District General Hospital and Medical College hospital of Amravati, Maharashtra. A total of 1394 patients were studied. Descriptive statistics like percentage and proportions were calculated. Proportions were compared using Chi square test of significance. Results: 86.7% were males and the maximum affected age group was 21 to 30 years. Majority of accidents were seen in summer season and on Monday of the week. Accidents were highest from 12 noon to 6 pm. Alcohol consumption was seen in 27% of the drivers. Two-wheelers were the commonest vehicle involved in RTAs. A total of 481 (34.5%) victims had fractures at various sites of the body, out of this 52.8% was of lower limbs. Right sided bony injuries were more common. Conclusions: There are multiple factors associated with RTAs which due to the lack of road safety measures in the country are playing their role. It is the need of the hour to address this issue and formulate rules and regulations and evaluate its enforcement.